White-tailed deer habitat in the Huautla Sierra, Morelos, Mexico - Hernández Silva, Dante Alfredo; Cortés Díaz, Enrique; Zaragoza Ramírez, José Luis; Martínez Hernández, Pedro Arturo; González Bonilla, Giovany Tonatiuh; Rodríguez Castañeda, Berta; Hernández Sedas, Dante Alfredo (Instituto de Ecología, A.C., 2011)
The study was conducted in three certified units for environmental management (UMA), these were Ajuchitlan-Santiopa, El Limon de Cuauchichinola and Pitzotlan, Morelos, Mexico, it lasted from March to August, 2007, and consisted in the evaluation of white-tailed deer (Odocoileus virginianus mexicanus Gmelin, 1788) habitat. To define the habitat tree and shrub composition was determined by central point quadrants, measures were diameter of tree canopy, plant density in 100 m2, accessibility of potential plants that are ingested by deer, altitude, slope, species importance and botanical familiesand richness indexes (Margalef and Menhinick), equity (Shannon, Inverse Shannon, Evenness) and dominance indexes (Simpson, Inverse Simpson, Berger-Parker and Inverse Berger-Parker). A total of 72 species were found, 29 botanical families, tree and shrub dominances were 68 and 32% respectively. Euphorbia schlechtendalii, Lysiloma divaricata and Acacia cochliacantha species showed the highest values in importance, abundance and even in anthropogenic use. The botanical family Fabaceae was the most wide spread and with the highest importance value among botanical families. From statistical analysis mean basal wasn’t different between UMA’s and transects (p > 0.05) as well as plant densityin 100 m2 (x _ = 23.44), the accessibility with a mean value of 0.48 m which was highly accessible to deer, areal tree cover of 8.89 m2 and the altitude; the slopes was different between UMA’s and transects (p < 0.05). The white-tailed deer habitat of the Sierra de Huautla with the best attributes is the one that shows high richness, abundance and no dominance of plant species and high slopes on the field; focus mainly on food availability and coverage.